6 - L’embouteillage dans Les Grandes Villes de L’Afrique de L’ouest et ses Problemes : Cas de Cotonou au Benin - Offin Lié Rufin Akiyo,; Julien Adounkpe,; Charles Lambert Babajide,; Ikililou Akobi,; Benoît N’bessa, (African Sociological Review, 2016)
This study focused on “”The congestion in the major cities of West Africa and its problems: Case Cotonou in Benin”aims to study the causes and socio-economic and environmental consequences of the congestion at the major arteries of the administrative capital of Benin especially during peak hours. And to achieve this, the data collection was conducted through desk research, direct and participatory observation, interview and field survey. After data processing, analysis of results is carried out following the PEIR model (Pressure, State, Impact, Response). Indeed, these different results, it follows that the concentration of administrative services in the city of Cotonou, the rural exodus, the defection of the road network and the proliferation of twowheeled vehicles in this study environment are the main causes bottling commonly called “Go Slow” with the main pole, the crossroads Akossombo. This situation causes serious harm not only the environment but also to the people of Benin. Among these nuisances, include among others the loss of time and in turn significant financial revenue not to mention the decline in Gross Domestic Product (GDP) for the State of Benin and for companies and societies. A whole wave of consequences, add air and noise pollution, the continuing development of certain diseases such as headaches, acute respiratory infections, lung cancer, stress, etc. Finally, to reduce a little bit different problems related to this phenomenon in the city of Cotonou in southern Benin, it is important that the authorities at various levels think about the construction of new road infrastructure, outsourcing of administrative services, businesses and companies to secondary cities, the grant of new vehicles, the creation and promotion of public ransportation, etc.